Hacia un nuevo modelo laboral en España - Cruz, Jesús (2012)
Towards a new labor model in SpainThe article starts with confirming the acceleration process in reforms of labor regulations-intensive and extensive-which is faced bySpain that has considered even the reform of constitutional framework. It should be noted that measures taken in the Spanish reform are aimed at increasing the employability of workers and with regard to promotion of employment stability; we find the incorporation of a new contractual modality, literally called “employment contract for indefinite time to support entrepreneurs”.Meanwhile, as the most important novelties are located the following: elimination with general character of administrative authorization for collective dismissals, the expansion of the proper reasons of economic dismissals, with the corresponding reduction effect of the judicial control as justification for business measure and the possible reduction in the practice of dismissal cost, the generalization of compensatory amount for unfair dismissal after 33 days of salary per year of seniority with limit of the 24 monthly salary, the complete suppression of processing salaries when the employer chooses indemnified extinction in case of unfair dismissal, among others. All this range of regulatory changes is analyzed critically by the author who, starting from the Spanish legislation, studies the most relevant legal concepts.